2014
DOI: 10.1177/0148607114528982
|View full text |Cite
|
Sign up to set email alerts
|

Physical Compatibility of Sodium Glycerophosphate and Calcium Gluconate in Pediatric Parenteral Nutrition Solutions

Abstract: It is recommended that NaGP replace sodium phosphate in PN solutions. This would eliminate the concern of calcium and phosphorus precipitation and the need of any saturation curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 11 publications
1
22
2
5
Order By: Relevance
“…A previous publication outlined the improved solubility of PN containing calcium gluconate when organic glycerophosphate is used in place of inorganic phosphate 15 . It was reported that PN containing up to 50 mEq/L calcium gluconate and 50 mmol/L NaGP was compatible.…”
Section: Discussionmentioning
confidence: 99%
“…A previous publication outlined the improved solubility of PN containing calcium gluconate when organic glycerophosphate is used in place of inorganic phosphate 15 . It was reported that PN containing up to 50 mEq/L calcium gluconate and 50 mmol/L NaGP was compatible.…”
Section: Discussionmentioning
confidence: 99%
“…In times of shortages of this additive, CaCl 2 may be considered as the preferred choice over CaGlu-Gl based upon its low Al content and the lack of evidence of adverse clinical effects associated with the use of CaCl 2 in neonatal PN. Another alternative is to use an organic phosphate such as sodium glycerophosphate (NaGP) as the phosphate additive with either CaGlu-PL or CaCl 2 since this phosphate additive is highly soluble with either calcium gluconate or calcium chloride [25,26]. At this time NaGP has only been approved for use in the U.S. when the mineral phosphates are unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…En pediatría el uso de fosfato orgánico permite poder alcanzar los requerimientos de forma segura (22)(23)(24)(25)(26). Para evitar el paso de posibles precipitados se recomienda el uso de filtros en la administración de la NP, ya que incluso con el uso de fuentes orgánicas de fosfato podrían producirse precipitados (27).…”
Section: Electrolitosunclassified